PASAR MODAL SYARIAH : ANALISIS PENAWARAN EFEK SYARIAH DI BURSA EFEK INDONESIA - AWALUDDIN AWALUDDIN (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The theme of the article is based on economic principles Islam. The purpose of writing the article is: to analyze the Sharia in BEI exchange offer. Research is the study of literature. The index of sharia has become a part or the instrument in capital market transactions. Any securities that enter the Islamic capital market flows through a rigorous selection on sharia indekk that JII (Jakarta Islamic Index). The selection is part of the bidding process before the Islamic securities offered to investors through the capital market. Among the sharia always dimanati index at the level of investors were shares of sharia, Islamic mutual funds, Islamic bonds (Sukuk) which is a part that can not be separated in capital market transactions. The institute is a precondition towards Islamic securities with principal business does not conflict with Islamic law, as stated in a fatwa DSN-MU. In the presence Index sharia, the Islamic banks, Takaful and other Islamic financial institutions have alternatives to invest their funds and distribute their profits to their clients.